Tingkat Keterampilan Motorik Kasar Pada Siswa Kelas IV Madrasah Ibtidaiyah Al Musthofa - Ilmul Ma’arif; Zakaria Wahyu Hidayat; Faisol Hamid; Grenda Yoga Pribadi (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2024)
This study was conducted with the aim of measuring the level of motor skills of fourth-grade students at MI Al Musthofa. This study was a quantitative descriptive study, and the method used in this study was a survey. The instrument used in this study was the Motor Ability Test for Elementary Schools, which included a 4 x 10 metre shuttle run test (agility), a 1-metre ball throw and catch test against a wall (coordination), a Stork Stand Positional Balance test (balance), and a 30-metre sprint test (speed). Data collection techniques used tests and measurements. The subjects used in this study were all 83 fourth-grade students at MI Al Musthofa. The data analysis technique used quantitative descriptive analysis with percentages. Based on the results of the study, it was found that the gross motor skills of MI Al Musthofa Canggu students were in the very good category 0%, good category 0%, moderate category 2.4%, poor category 18.1%, and very poor category 79.5%. The conclusion of this study is that the gross motor skills of students are in the very poor category.